Despite weaker job market, Germany's economic upswing continues - Ferdinand Fichtner; Karl Brenke; Marius Clemens; Simon Junker; Claus Michelsen; Maximilian Podstawski; Thore Schlaak; Kristina van Deuverden (DIW Economic Bulletin, 2016)
In spite of persisting unfavorable external economic conditions, the German economy's upward trend continues, with a growth of 1.2 percent expected for the coming year - slightly less than the 1.8 percent growth rate of 2016, a difference primarily due to the fact that 2017 has fewer workdays. A growth rate of 1.6 percent is expected for 2018. Although employment growth has slowed down somewhat since this past summer, private consumption remains the German economy's primary growth driver - but given the higher inflation, this dynamic will lose momentum in the course of the coming quarters. Exports are picking up in the moderately recovering global economy, and this will be even more noticeable lateron in the forecast period. Though investment activity will be somewhat stimulated by the improvement in foreign demand, it will remain rather modest.
Keywords: E32; E66; F01; 330; business cycle forecast; economic outlook